The Impact of Sleep Quality on Clinical Outcomes in Hospitalized Children: A Systematic Review - Mella Mardison Putri; Nani Nurhaeni; Astuti Astuti (GLOBAL HEALTH SCIENCE GROUP, 2026)
Sleep is an essential physiological need in children that plays an important role in physical growth, neurological development, and the recovery process during illness. Hospitalized children are at high risk of experiencing sleep quality disturbances due to environmental, clinical, and psychological factors. Sleep disturbances during hospitalization are known to be associated with various adverse clinical outcomes. To identify the relationship between sleep quality and clinical outcomes in hospitalized children based on the latest scientific evidence. This systematic review was conducted in accordance with the PRISMA guidelines. Literature searches were performed in PubMed, ScienceDirect, Scopus, and Wiley. “poor sleep quality” AND “hospitalized children” AND “length of stay.” Included studies were quantitative studies involving hospitalized children aged 0–18 years that reported the relationship between sleep disturbances and clinical outcomes. Study quality was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist, and the findings were analyzed using narrative synthesis. A total of six studies years 2021-2026 met the inclusion criteria. All studies reported decreased sleep quality during hospitalization, characterized by reduced sleep duration, increased nighttime awakenings, and decreased sleep efficiency. Sleep disturbances were associated with slower recovery, increased psychological distress, and a potential increase in length of hospital stay. The main contributing factors include environmental noise, medical interventions, pain, and anxiety. Non-pharmacological interventions were found to be effective in improving sleep quality. Sleep quality disturbances are common and multifactorial problems among hospitalized children and have a significant impact on clinical outcomes. Optimizing sleep quality should be integrated into clinical practice through simple interventions and family-centered approaches.